Acute mechano-electronic responses in twisted phosphorene nanoribbons. Issue 31 (22nd July 2016) - Jang, Woosun; Kang, Kisung; Soon, Aloysius
Abstract : A first-principles study of the anisotropic, chirality-dependent mechano-electronic responses in hydrogen-passivated twisted one-dimensional phosphorene nanoribbons. Abstract : Many different forms of mechanical and structural deformations have been employed to alter the electronic structure of various modern two-dimensional (2D) nanomaterials. Given the recent interest in the new class of 2D nanomaterials – phosphorene, here we investigate how the rotational strain-dependent electronic properties of low-dimensional phosphorene may be exploited for technological gain. Here, using first-principles density-functional theory, we investigate the mechanical stability of twisted one-dimensional phosphorene nanoribbons (TPNR) by measuring their critical twist angle ( θ c ) and shear modulus as a function of the applied mechanical torque. We find a strong anisotropic, chirality-dependent mechano-electronic response in the hydrogen-passivated TPNRs upon vortical deformation, resulting in a striking difference in the change in the carrier effective mass as a function of torque angle (and thus, the corresponding change in carrier mobility) between the zigzag and armchair directions in these TPNRs. The accompanied tunable band-gap energies for the hydrogen-passivated zigzag TPNRs may then be exploited for various key opto-electronic nanodevices.